Am I lazy, a drama queen or depressed? A journey through a pluralistic approach to analysing accounts of depression. Issue 2 (3rd April 2022) - Dempsey, Maria; Foley, Sarah; Frost, Nollaig; Murphy, Raegan; Willis, Niamh; Robinson, Sarah; Dunn-Galvin, Audrey; Veale, Angela; Linehan, Carol; Pantidi, Nadia; McCarthy, John
ABSTRACT: The application of Pluralism in Qualitative Research (PQR) allows for a multi-perspective approach to understanding the nuanced social and psychological phenomenon. The complexity of what it means to qualitatively analyse and respond to sensitive data from the reflexive position of the analyst, is the focus of this paper. We introduce previous work in pluralism, and data from ReachOut.com, an online resource for young people in need of mental health advice in Ireland. We present our analysis of the posts from ReachOut.com which conveys the varied understandings of depression, from a medically understood illness, to a socially constructed lived experience. Analysis of the reflexive positioning of our group of experienced qualitative researchers highlights the need for support for those who engage with such data. Our findings reflect the outcomes and experience of using pluralism to examine mental health concerns which require further social, cultural and technological responses.